The utility of non‐invasive tests to assess advanced fibrosis in Asian subjects with chronic hepatitis B and concomitant hepatic steatosis - Lin, Kenneth W.; Kumar, Rajneesh; Shen, Feng; Chan, Henry L.‐Y.; Wong, Grace L.‐H.; Kumar, Rahul; Chow, Wan Cheng; Lin, Su; Wong, Vincent W.‐S.; Fan, Jian‐Gao; Goh, George B.‐B. (Liver international, 2023)
Background Chronic hepatitis B (CHB) is endemic to Asia and is a leading cause of liver‐related morbidity. The prevalence of concomitant CHB and hepatic steatosis (HS) is increasing in Asia. Non‐invasive tests (NITs) including FIB‐4, NFS and APRI assess fibrosis in populations with a single aetiology, but not in subjects with concomitant CHB and HS. Aim To explore the accuracy of NITs in predicting advanced fibrosis in patients with concomitant CHB and HS. Methodology This multicentre study of CHB patients who underwent liver biopsy explored clinical characteristics of these subjects, stratified by presence of HS. Fibrosis scores from NITs were compared against histological fibrosis stage in CHB subjects with and without HS. Results 2262 subjects were enrolled, 74.5% were males, and the mean age was 39.5 years ±11.8 SD. 984 (44.4%) had HS, 824 (36.4%) had advanced fibrosis. In the CHB group, the AUROC for advanced fibrosis were 0.65 (95% CI 0.62–0.69) for FIB‐4 and 0.63 (95% CI 0.60–0.66) for APRI. The specificities were 0.94 for FIB‐4 greater than 3.25 and 0.81 for APRI greater than 1.5. In the CHBHS group, the AUROC for advanced fibrosis were 0.67 (95% CI 0.63–0.71) for FIB‐4, 0.60 (95% CI 0.56–0.64) for APRI and 0.65 (95% CI 0.61–0.69) for NFS. The specificities were 0.95 for FIB‐4 greater than 3.25, 0.88 for APRI greater than 1.5 and 0.99 for NFS greater than 0.675. Conclusion The performance of NITs to exclude advanced fibrosis did not differ greatly regardless of HS. FIB‐4 and NFS have the best negative predictive values of 0.80 and 0.78, respectively, to exclude advanced fibrosis in CHBHS subjects.